Functional role of induced gamma oscillatory responses in processing noxious and innocuous sensory events in humans. (3rd December 2015) - Liu, C.C.; Chien, J.H.; Chang, Y.W.; Kim, J.H.; Anderson, W.S.; Lenz, F.A.
Highlights: Signals are directly recorded from the surface of the brain covering large brain areas. Specificity of gamma time–frequency responses (TFRs) was tested in humans. Gamma TFRs were attention related. Gamma TFRs were not modality specific. The observed gamma TFRs were induced and not evoked. Abstract: Gamma time–frequency responses (TFRs) induced by painful laser in the contralateral primary somatosensory (SI) cortex have been shown to correlate with perceived pain-intensity in human. Given the functional roles of gamma TFRs in the cortical spaces, it remains unclear whether such a relationship is sustained for other brain regions where the laser-evoked potentials (LEPs) are presented. In this study, we delivered the painful laser pluses at random pain-intensity levels (i.e. strong, medium and weak) in a single train to the dorsal hand of six patients with uncontrolled epilepsy. The laser stimulus produced a painful pinprick sensation by activating nociceptors located in the superficial layers of the skin. For each patient, arrays of >64 subdural electrodes were implanted directly covering the contralateral SI, parasylvian (PS) and medial frontal (MF) cortices to study the stimulus related gamma (TFRs) in the neocortex. In addition, using the same stimulation paradigm, the modality specificity of gamma TFRs was further examined by applying innocuous vibrotactile stimuli to the same regions of the dorsal hand in a separated group of five patients. Our results showed that gamma TFRs are not modality specific, but the largest gamma TFRs were consistently found within the SI region and noxious laser elicited significantly stronger gamma TFRs than innocuous nonpainful vibratory stimuli. Furthermore, stronger pain induced stronger gamma TFRs in the cortices of SI ( r = 0.4, p < 0.001) and PS ( r = 0.29, p = 0.005). Given that potentially harmful noxious stimulus would automatically capture greater attention than the innocuous ones, our results support the hypothesis that the degree of SI and PS gamma TFRs is associated with an attentional drive provoked by painful stimuli.